Metabolomic investigations into human apocrine sweat secretions - Mullard, Graham (2012)
Human axillary odour is formed by the action of Corynebacteria or Stephyloccui bacteria on odourless axilla sections. Several groups have identified axillary odorants, including 3-methyl-2-hexanoic acid (3M2H) and 3-hydroxy-3-methyl-hexenoic acid (HMHA), and how they are pre-formed and bound to amino acid conjugates. However, there is currently a lack of LC-MS methodologies and no reported NMR methods, that are required to further identify the non-volatile constituents, which would provide further information to allow understanding of the underlying physiological biochemistry of malodour.